Perception and Clinical Outcomes of Arthrodesis and Contralateral Total Ankle Replacement for Ankle Osteoarthritis: A Narrative Review - Vyara Harizanov; Luisa Daniela Castillo-Rodríguez; Carlos Alberto Sánchez-Correa (Journal of the Foot & Ankle, 2026)
Objective: To evaluate the current evidence on perception, satisfaction, and functional outcomes in patients with bilateral ankle osteoarthritis treated with a total ankle replacement on one limb and contralateral arthrodesis. Methods: This narrative review, conducted as a qualitative, descriptive thematic synthesis in accordance with the Scale for the Assessment of Narrative Review Articles, searched four electronic databases between March and April 2026 with no restriction on publication year. The intra-individual design was intended to reduce demographic and lifestyle heterogeneity, although it does not eliminate biomechanical interdependence between limbs. Results: Three studies met the inclusion criteria, with mean follow-up ranging from 2 to 6.2 years across cohorts. Both procedures achieved comparable pain relief. Total ankle replacement preserved sagittal-plane motion, producing higher functional scores and a more intuitive, physiologic gait, whereas arthrodesis offered a stable weight-bearing base but restricted dorsiflexion, induced compensatory midfoot kinematics, and increased the cognitive burden of monitoring the environment to prevent falls. Patientreported and general health measures showed comparable satisfaction between sides; replacement complications were predominantly mechanical, whereas arthrodesis complications were predominantly biological. The hybrid strategy was reported as more cost-effective than bilateral arthroplasty. Conclusion: In bilateral end-stage ankle osteoarthritis, combining a replacement on one limb with a contralateral arthrodesis allows patients to alternate limb use according to task; standardized, long term prospective studies are required to confirm these observations. Level of Evidence V; Narrative review